The Pros and Cons of Third Party Funding in the International Investment Arbitration Regime - Mirveisi, Alireza; Zakerian Amiri, Mehdi; Abdollah Zadeh, Mohammad Ali (Public Law Researsh, 2023)
There is a growing stream of critics who see investment arbitration in favor of foreign investors and as a negative force as opposed to sustainable development. The phenomenon of third-party funding and its use in investment arbitration has increased such concerns. Third-party funding is basically the payment of all or a part of the arbitration costs of one of the parties of dispute by a third party funder which in return, the funder receives a percentage of the output of the award if successful. The purpose of this article is to explain and analyze the theoretical differences between pros and cons of third-party funding regarding the access to justice, screening mechanism for the claims, and the financial consequences on the host state. In this article, the advocates see third-party funding as a means of access to justice for aggrieved investors in investment claims, while the adversaries refering on the profitability of third-party funding, see this method in arbitration a form of wealth transfer from public sector to private corporations and also refer to the asymmetric structure of the investment arbitration regime as well as the risks arising from the transfer of management and control of arbitration process to the third party funders. یک جریان رو به رشدی از منتقدان وجود دارد که داوری سرمایه‌گذاری را به نفع سرمایه‌گذاران خارجی و بعنوان یک نیروی منفی در تضاد با توسعه پایدار می‌داند. پدیده تأمین مالی ثالث و بکارگیری آن در داوری سرمایه‌گذاری به این نگرانی‌ها افزوده است. تأمین مالی ثالث اساساً پرداخت تمام یا بخشی از هزینه‌های داوری یکی از طرفین دعوی توسط تأمین کننده شخص ثالث است که در ازای آن، تأمین کننده مالی درصدی از رأی صادره را در صورت پیروزی دریافت می‌نماید. هدف مقاله، تشریح و تحلیل اختلافات نظری موافقان و مخالفان تأمین مالی ثالث در خصوص دستیابی به عدالت، غربالگری دعاوی و تبعات مالی آن بر دولت است. در این مقاله موافقان، تأمین مالی ثالث را ابزاری جهت دستیابی به عدالت برای سرمایه‌گذاران زیان‌دیده در دعاوی سرمایه‌گذاری در نظر می‌گیرند در حالی که مخالفان با اتکا به اهداف سودآوری تأمین مالی ثالث، این روش را در داوری نوعی انتقال ثروت از بخش عمومی به بخش خصوصی می‌دانند و به ساختار نامتقارن رژیم داوری سرمایه‌گذاری و خطرات ناشی از انتقال مدیریت و کنترل فرایند داوری به تأمین کنندگان شخص ثالث نیز اشاره می‌نمایند.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitragem; Arbitration; Investment Arbitration Regime; Investments; Screening Mechanism for Claims; Third Party Funding; تأمین مالی ثالث; دستیابی به عدالت; رژیم داوری سرمایه‌گذاری; غربالگری دعاوی

The Right to Water in Investment Treaty Arbitration and Its Impact on Jurisdiction and Applicable Law - Geravand, Farshad (Public Law Researsh, 2022)
The right to water in investment arbitration has been one of the most contentious issues before investment arbitration tribunals in recent decades. The privatization of public services, including water and sanitation, and assigning them to foreign investors has caused the right to water as a vital benefit being repeatedly raised in investment arbitrations. However, due to tribunals’ narrow interpretation of jurisdiction and applicable law, this fundamental human right has been considered irrelevant and ignored, and this has fueled the legitimacy crises in investment arbitration. This research seeks to indicate the potentiality of more protection of the right to water through balancing the states international obligations in the two areas of investment law and human rights law. Proposed methods for integrating human rights with investment law include the correct interpretation of jurisdictional clauses and the applicable law based on the treaties interpretation principles, systematic integration and the inclusion of new clauses in investment agreements. طرح حق بر آب در داوری سرمایه‌گذاری یکی از مناقشه‌انگیزترین مباحث پیش روی دیوان‌های داوری در چند دهه اخیر بوده است. خصوصی‌سازی خدمات عمومی از جمله آب و فاضلاب و سپردن آنها به سرمایه‌گذاران خارجی موجب شده تا حق بر آب بعنوان یک منفعت عمومی و حیاتی بارها در داوری‌های سرمایه‌گذاری مطرح شود. با تفسیر مضیق محاکم از شروط صلاحیتی و قانون حاکم، این حق بنیادین بشری در برخی موارد نامربوط و نادیده تلقی شده و این امر به بحران مشروعیت در داوری سرمایه‌گذاری دامن زده است. این جستار می‌کوشد تا امکان حمایت بیشتر از حق بر آب را از طریق برقراری تعادل بین تعهدات بین‌المللی دولت‌ها در دو عرصه حقوق سرمایه‌گذاری و حقوق بشر نشان دهد و در پایان روش‌هایی را برای ادغام این دو از جمله تفسیر درست شروط صلاحیتی و قانون حاکم با تکیه بر اصول تفسیر معاهدات، تلفیق سیستمیک و گنجاندن بندهای جدید در موافقتنامه‌های سرمایه‌گذاری پیشنهاد کند.
Keywords: Applicable law; International Investment Arbitration; Jurisdiction; Right to Water; Systemic Integration; تلفیق سیستمیک; حق بر آب; داوری سرمایه‌گذاری بین‌المللی; شروط صلاحیتی; قانون حاکم

Role of Abuse of Rights Doctrine and Investment Arbitration Ratione Temporis in Limiting Nationality Planning - Saeedi, Niloofar; Askary, Pouria (Public Law Researsh, 2022)
Sometimes foreign investors after the dispute have arisen or when it is predictable and with the intention of bringing the dispute to arbitration, change their nationality or acquire new nationality. The phenomenon called Nationality Planning eases foreign investors’ access to a desirable treaty and increases the chance of bringing disputes against host states.So host states try to avoid these disputes by raising objections to Ratione Temporis or claiming abuse of rights. Arbitration tribunals’ approach towards their Ratione Temporis and abuse of rights is material in host states’ success in limiting Nationality Planning. So the question to be answered is that what requirements are considered by arbitrations in determining Ratione Temporis and abuse of rights and how these two are different. Arbitral precedent shows that these tribunals make distinction between cases of nationality planning contrary to their Ratione Temporis and cases that are considered as abuse of rights. However, in practice their strict approach results in limited acceptation of objections to Ratione Temporis or abuse of rights claims. گاه سرمایه‌گذار خارجی پس از بروز اختلاف یا زمانی که اختلاف قابل پیش‌بینی است و به قصد طرح دعوی در مرجع داوری، اقدام به تغییر تابعیت یا کسب تابعیت جدید می‌نماید. این اقدام که برنامه‌ریزی تابعیت نام دارد، دسترسی سرمایه‌گذار خارجی به یک معاهده سرمایه‌گذاری مطلوب را تسهیل کرده و احتمال طرح دعوی علیه دولت میزبان را افزایش می‌دهد. از این‌رو دولت‌های میزبان تلاش می‌کنند با طرح ایراد به صلاحیت زمانی یا سوء استفاده از حق، مانع پذیرش چنین دعوایی شوند. رویکرد مراجع داوری در احراز صلاحیت زمانی خود و تشخیص موارد سوء استفاده از حق، در موفقیت یا عدم موفقیت دولت میزبان در مقابله با برنامه‌ریزی تابعیت تعیین‌کننده است. بنابراین باید به این پرسش پرداخته شود که مراجع داوری چه شرایطی را برای احراز صلاحیت زمانی و سوء استفاده از حق در نظر می‌گیرند و چگونه میان این دو تمایز قائل می‌شوند. رویه مراجع داوری حاکی از آن است که این مراجع میان مواردی از برنامه‌ریزی تابعیت که مانع صلاحیت زمانی آن‌هاست و مواردی که سوء استفاده از حق تلقی می‌گردد، تمایز قائل می‌شوند. هرچند رویکرد سخت‌گیرانه آنها در عمل موجب می‌شود تنها در موارد محدودی ایراد به صلاحیت زمانی یا ادعای سوء استفاده از حق مورد پذیرش واقع شود.
Keywords: Abuse of rights; Bilateral Investment Treaty; Foreign Investment Arbitration; Nationality Planning; Ratione Temporis; برنامه‌ریزی تابعیت; داوری سرمایه‌گذاری خارجی; سوء استفاده از حق; صلاحیت زمانی; معاهده دوجانبه سرمایه‌گذاری

Scope of Obligation of the Host State for Protection of Foreign Investor in Armed Conflicts - Shahbazian, Abolghasem; Salimi, Sadegh (Public Law Researsh, 2022)
Measures taken by governments during armed conflict to safeguard their essential interests sometimes cause damages to foreign investors. The investors thus affected seek remedies in the arbitration tribunals invoking breach of host government obligations to protect investments. The host government also usually attempts to assert as defense non-precluded measures to prove its irresponsibility, or if it proves responsible, justify it by resorting to circumstances precluding wrongfulness in the customary international law. But since different courts do not consider the same requirements to invoke these rules, there is no certainty that the parties to the lawsuit will be able to invoke them and, as a result, the scope of government's obligations to protect the foreign investor during the armed conflict is obscure. To clarify the scope of the host government's obligations to protect the foreign investor during armed conflicts and balance the interests of the investor and the host government during the investment disputes arising from the armed conflict, this article explores the possibility and requirements of invoking circumstances precluding wrongfulness and non-precluded measures and the relationship between them. اقداماتی که دولت‌ها در زمان مخاصمات مسلحانه در جهت حفظ منافع اساسی خود انجام می‌دهند گاه موجب ورود خسارت به سرمایه‌گذاران خارجی می‌گردد. سرمایه‌گذاران آسیب‌دیده در محاکم داوری با استناد به نقض تعهدات حمایتی توسط دولت میزبان، خسارات وارده به خود را طلب می‌نمایند. دولت میزبان نیز معمولاً برای اثبات عدم مسئولیت خود به شرط اقدامات منع نشده مندرج در معاهده سرمایه‌گذاری استناد می‌کند و یا در صورت اثبات مسئولیت، به منظور توجیه آن به معاذیر رافع وصف متخلفانه در حقوق بین‌الملل عرفی متوسل می‌شود. اما از آنجا که محاکم مختلف، شرایط یکسانی را جهت استناد کشور میزبان به شرط اقدامات منع نشده و معاذیر رافع وصف متخلفانه در نظر نمی‌گیرند، قطعیتی در امکان استناد به آن‌ها وجود ندارد. در نتیجه، قلمرو تعهد دولت به حمایت از سرمایه‌گذار خارجی در زمان مخاصمات مسلحانه در هاله‌ای از ابهام فرو رفته است. این مقاله با هدف روشن ساختن قلمرو تعهد دولت میزبان به حفاظت از سرمایه‌گذار خارجی در هنگام مخاصمات مسلحانه و به منظور توازن منافع سرمایه‌گذار و دولت میزبان در دعاوی سرمایه‌گذاری ناشی از مخاصمات مسلحانه، امکان و الزامات استناد کشور میزبان به معاذیر عرفی رافع وصف متخلفانه و شرط اقدامات منع نشده و ارتباط میان آنها را مشخص می‌نماید
Keywords: Armed Conflicts; Customary International Law; Foreign investment; Interests of the Host State; Non-Precluded Measures; اقدامات منع نشده; حقوق بین‌الملل عرفی; سرمایه‌گذاری خارجی; مخاصمات مسلحانه; منافع دولت میزبان

The Relationship between International and Domestic Law in the Field of Attribution of Responsibility to a State in International Investment Disputes - Amidimehr, Elham; Seifi, Jamal (Public Law Researsh, 2021)
The attributability of actions to states within the context of investment treaty disputes and to focus on the roles played by international and domestic laws in such attributions have caught the attention of jurists in recent years. The ILC Draft Articles on Responsibility of States for Internationally Wrongful Acts, and particularly, article 3 points to the main outcome of this debate, where it does not consider domestic law irrelevant in internationally wrongful acts and stipulates that the issue is subject to international law and it will take into account the relevance of domestic law. Thus, although the characterization of an act of a State as internationally wrongful is an independent function of international law and such characterization is not affected by the characterization of the same act as lawful by domestic law, it does not mean that domestic law is irrelevant to such description; on the contrary, it may be related in various ways. The present article attempts to examine the challenging junction of domestic and international law with regard to the attributability of actions taken within the framework of investment treaties, specifically by state-owned and para-statal entities that exercise elements of state authority. قابلیت انتساب عمل به دولت در چارچوب اختلافات معاهده‌ سرمایه‌گذاری و تمرکز بر نقش‌هایی که حقوق بین‌الملل و حقوق داخلی در چنین انتسابی ایفا ‌می‌نمایند در زمره‌ مباحثی است که در سال‌های اخیر بسیار مورد ‌توجه حقوقدانان بوده و ماده 3 مواد کمیسیون حقوق بین‌الملل در ارتباط با مسئولیت دولت‌ها نیز بیانگر پیامد اصلی این بحث است که فی‌الواقع، حقوق داخلی را با مسأله متخلفانه بودن اعمال از حیث بین‌المللی بی‌ارتباط تلقی ‌ننموده، بلکه مقرر ‌می‌دارد مسئله مورد بحث، تابع حقوق بین‌الملل است لیکن حقوق بین‌الملل نیز خود تا حدِ ارتباط، حقوق داخلی را در نظر خواهد گرفت. بنابراین اگرچه توصیف خصوصیات یک عمل به عنوان عملی غیرقانونی از عملکردهای مستقل حقوق بین‌الملل است که تحت ‌تأثیر توصیف خصوصیات این عمل بموجب حقوق داخلی قرار نمی‌گیرد لیکن این گفته بدین معنی نیست که حقوق داخلی با توصیف عمل متخلفانه‌ بین‌المللی بی‌ارتباط ‌است؛ بالعکس، ممکن ‌است به طرق مختلفی به آن مرتبط‌ باشد. در این مقاله سعی بر‌ آن است که تلاقی چالش‌برانگیز حقوق داخلی و حقوق بین‌الملل در بحث قابلیت انتساب اعمال ‌صورت ‌گرفته در چارچوب معاهدات سرمایه‌گذاری توسط ارگان‌های دولتی و نهادهای نیمه‌دولتی که عناصر اختیارات دولتی را اعمال می‌نمایند مورد واکاوی قرار‌ گیرد.
Keywords: Attribution; Domestic Law; International Arbitration; International Investment Treaties; International Law; حقوق بین‌الملل; حقوق داخلی; داوری بین‌المللی; معاهدات سرمایه‌گذاری بین‌المللی; کلیدواژگان انتساب مسئولیت

A Reflection on the Invalidation of Patents in the Light of Constituent Elements of Indirect Expropriation under Foreign Investment Law - Rahbari, Ebrahim; Shahabi, Mahdi; Falahati, Soroosh (Public Law Researsh, 2021)
Patents are considered as investments protected under the International Investment Law. Although, these properties are protected under the principle of territoriality, similar to other investments, they can be expropriated as a result of host states’ regulatory measures inconsistent with protection standards stemming from foreign investment protection regulations and treaties including fair and equitable treatment and legitimate expectations of foreign investors. Considering the fact that few arbitration awards have been issued by arbitration panels in this regard, it is yet difficult to claim there is a strong precedent in International Investment Law. Nevertheless, reflecting the provisions of international regulations, the stance of the domestic law and the most important relevant case, this article provides the most significant elements of indirect expropriation as well as existing doctrines in this respect and further investigates whether invalidation of patents can amount to indirect expropriation. It will also be mentioned that despite the fact that according to several foreign investment protection treaties, invalidation of patents shall not be subject to regulations regarding indirect or creeping expropriation, the final determination lies with the arbitration panel. یکی از مصادیق سرمایه‌گذاری خارجی مورد حمایت در حقوق بین‌الملل سرمایه‌گذاری، اختراعات است. این دسته از دارایی‌ها علی‌رغم به رسمیت شناخته شدن در پرتو اصل سرزمینی بودن حمایت، همانند سایر سرمایه‌گذاری‌ها می‌توانند تحت تدابیر حاکمیتی دول میزبان که مغایر با استانداردهای حمایتی نشأت گرفته از قوانین و معاهدات بین‌المللی حمایت از سرمایه‌گذاری خارجی همچون شرط رفتار عادلانه و منصفانه و صیانت از انتظارات مشروع و معقول سرمایه‌گذار می‌باشند، با خطراتی همچون سلب مالکیت مواجه شوند. نظر به صدور آرای معدود مراجع بین‌المللی در این خصوص، سخن گفتن از شکل‌گیری رویه‌ای متقن در این راستا دشوار می‌باشد. با این حال، در این نوشتار ضمن بررسی مهمترین عناصر متشکله سلب مالکیت غیرمستقیم و دکترین‌های موجود در این زمینه، به بررسی قابلیت تطبیق ابطال گواهی ثبت اختراع با سلب مالکیت غیرمستقیم پرداخته و با تشریح مقررات برخی اسناد بین‌المللی، موضع حقوق داخلی و مهم‌ترین پرونده مربوط به این موضوع در حقوق سرمایه‌گذاری خارجی در ابعاد گوناگون آن مداقه نموده و در نهایت به این نتیجه خواهیم رسید که حتی در صورت مستثنی نمودن ابطال گواهی ثبت اختراع از مقررات مربوط به سلب مالکیت در معاهدات حمایت از سرمایه‌گذاری خارجی، تشخیص نهایی تحقق سلب مالکیت با دیوان داوری است.
Keywords: Elements of indirect expropriation; Foreign investment; Indirect expropriation; Intellectual property; Invalidation of patents; ابطال گواهی ثبت اختراع; حقوق مالکیت فکری; سرمایه‌گذاری خارجی; سلب مالکیت غیرمستقیم; عناصر سلب مالکیت غیرمستقیم